Important Role of Entrepreneurship Readiness in Education - Irni Istiqomah; Suparji; Marniati (Indonesia Approach Education, 2022)
Entrepreneurial skills, market orientation, and networking have a positive influence on entrepreneurial competence. Then entrepreneurial competence and entrepreneurial skills and networking have a positive influence on business performance. There is a significant influence of entrepreneurial competence in relation to entrepreneurial skills, marketing, networking and business workers. Entrepreneurship education in tourism is very important to improve the innovation skills of entrepreneurs in a dynamic environment. There is a positive impact of entrepreneurship education on business. Seeing the urgency of entrepreneurship education, therefore this article aims primarily to discuss the importance of entrepreneurship readiness in education. The reason why entrepreneurship education is included in the school curriculum and students should not be ruled by people or the government but they create jobs for themselves, this will also provide benefits for social and community welfare.